How Do We Do This? Distance Learning in Physical Education — Part 1. Issue 4 (4th May 2021) - Daum, David N.; Goad, Tyler; Killian, Chad M.; Schoenfeld, Amanda
Abstract: The COVID-19 pandemic has been a source of stress and anxiety to physical educators. This is likely due to school schedule changes, job security, balancing work and family commitments, and trying to navigate how to teach physical education in a distance learning format. Governments, schools, teachers, and families have been navigating the complexity of the mass shift to distance learning. The purpose of this feature is to address some frequently asked questions about teaching physical education remotely. Specifically, this article addresses meeting the needs of low-income students, at-home equipment strategies, teaching elementary physical education remotely, parent/guardian engagement, and building and maintaining relationships online. The social connectedness between teacher-student and student-student, which is inherently lacking in distance learning, is an important consideration for teachers. It is essential that teachers address the social needs for themselves and their students during remote teaching and learning. To adequately address each question, connections to research are made in addition to identifying best practices and instructional resources. Although the pandemic has created uncertain times, educators are resilient and will find a way to overcome barriers to meet the needs of their learners to achieve quality learning outcomes.